2019
DOI: 10.1186/s40497-019-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of need satisfaction for solo self-employed individuals’ vs. employer entrepreneurs’ affective commitment towards their own businesses

Abstract: Persistence in self-employment is crucial for entrepreneurial activities to generate longterm economic benefits. Consequently, this research examined the commitment of the self-employed towards their business as an important determinant of persistence. However, this research treats the self-employed as one entity. Yet we assume that especially for the research on commitment the differentiation of the self-employed into solo self-employed individuals (self-employed individuals without employees) and employer en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Moreover, the self-employed may not be any better. Although research has generally indicated that the self-employed tend to be happier, many individuals are engaged in what has been called precarious self-employment (Kottwitz et al, 2017;Schummer et al, 2019) especially those doing business in the informal sector and the solo selfemployed. These are challenged by long working hours, the burden of bearing risks, and having little social protection that affects the psychological wellbeing of entrepreneurs and the self-employed (Baron et al, 2016;Otto, Baluku, Hünefeld, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the self-employed may not be any better. Although research has generally indicated that the self-employed tend to be happier, many individuals are engaged in what has been called precarious self-employment (Kottwitz et al, 2017;Schummer et al, 2019) especially those doing business in the informal sector and the solo selfemployed. These are challenged by long working hours, the burden of bearing risks, and having little social protection that affects the psychological wellbeing of entrepreneurs and the self-employed (Baron et al, 2016;Otto, Baluku, Hünefeld, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, literature is silent on entrepreneurs’ intention to stay in their roles for a long time. Patel and Thatcher (2014) labeled this phenomenon as persistence in self-employment, while other researchers have investigated it in terms of commitment to one’s own business ( Felfe et al, 2008 ; Baluku et al, 2018a , b ,; Schummer et al, 2019 ). Persistence in entrepreneurial work is important for realization of the economic benefits of entrepreneurship since these tend to accrue in the long term than in the short term ( Baluku et al, 2018a ; Schummer et al, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Patel and Thatcher (2014) labeled this phenomenon as persistence in self-employment, while other researchers have investigated it in terms of commitment to one’s own business ( Felfe et al, 2008 ; Baluku et al, 2018a , b ,; Schummer et al, 2019 ). Persistence in entrepreneurial work is important for realization of the economic benefits of entrepreneurship since these tend to accrue in the long term than in the short term ( Baluku et al, 2018a ; Schummer et al, 2019 ). Having the intention to stay in this form of employment, which reflects the commitment to the form of employment ( Felfe et al, 2008 ) generates higher morale and effort, hence an essential attitude that can stimulate attainment of other work outcomes ( Felfe et al, 2008 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Solo self-employment can be defined as operating a business and having the sole responsibility for one's economic success without employing others for technical or professional support. Solo self-employed people have to be differentiated from employer entrepreneurs who are self-employed as well but utilize personnel (Schummer et al, 2019). Notably, to be counted as solo self-employed for tax purposes in Germany, helping family members as well as other services (e.g., cleaning staff) are not counted (Brenke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Small business owners are more strongly responsible for creating their working conditions (on their own) favorably as compared to employed people or employer entrepreneurs (i.e., self-employed people with personnel; Schummer et al, 2019 ). Also, when it comes to health, stress and strain have individual differences.…”
Section: Introductionmentioning
confidence: 99%